2012
DOI: 10.2214/ajr.11.7012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Severity of Carpal Tunnel Syndrome and Color Doppler Sonography Findings

Abstract: Our study suggests that the severity of CTS strongly correlates with color Doppler sonography findings, and this technique may represent a reliable complementary tool in CTS examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 18 publications
2
53
2
2
Order By: Relevance
“…To compensate, perineural veins may dilate and cause hyperemia and hypervascularization, which could be detected by NMUS [35]. We found hypervascularization in the median nerve in 16 patients and in the peroneal nerve in 7 patients.…”
Section: Discussionmentioning
confidence: 73%
“…To compensate, perineural veins may dilate and cause hyperemia and hypervascularization, which could be detected by NMUS [35]. We found hypervascularization in the median nerve in 16 patients and in the peroneal nerve in 7 patients.…”
Section: Discussionmentioning
confidence: 73%
“…A significant correlation between nerve cross-sectional area and all conventional measures of CTS severity, including clinical scales, hand function, and neurophysiological classification, has been found [43] in some but not all studies. Of interest, a recent study reported that hypervascularity, detected by ultrasound, correlated with the severity of nerve damage, assessed by neurophysiology [36, 37]. …”
Section: Compressive Neuropathymentioning
confidence: 99%
“…10 Normal and pathologic reference values for the cross-sectional area of the median nerve have been suggested, with the upper limit of normal generally approximating 9 mm 2 at the carpal tunnel. 1518 …”
mentioning
confidence: 99%